REACTION OF 3,5-DIMETHYLHEPTADIINE-1,6-DIOL-3,5 WITH ACETYLENE BY HETEROGENEOUS-CATALYTIC METHOD - Yusupova Lola Azimovna; Ergashev Jasur Rahimjon ugli; Abdullayev Muslimbek Chori ugli; Nurmonov Suvonkul Erxonovich (Scholar Express Journal, 2022)
The catalyst was obtained by impregnating an alkaline solution with activated carbon. The vinylation process with 3,5-dimethylheptadiine-1,6-diol- 3,5 with acetylene was carried out in a heterogeneous catalytic manner. The influence of the catalytic nature of the starting materials on the yield of vinyl ethers, the molecular ratio, the temperature and duration of the reaction was investigated.
Keywords: Acetylene; heterogeneous catalysis, 3; ,5-dimethylheptadiine-1,